2014
DOI: 10.11113/jt.v70.3517
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Content, Antioxidant and Antibacterial Properties of Scurrula ferruginea Extracts

Abstract: Discovery of new therapeutic agents from nature, especially plants is one of the promising approaches for treatment of various diseases. In traditional medicine Scurrula ferruginea is applied to treat some disorders. To the best of our knowledge, there are no investigations on antioxidant capacity and antimicrobial activities of S.ferruginea in Malaysia. The present study was conducted to determine total phenolic content, Fe2+ chelating activity, antioxidative and antimicrobial potential of flowers, leaves and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…This assumption in-line with others that majority of antioxidant compounds present in plants are secondary metabolitesphenolic compounds (tannins, flavonoids, and phenolic acids) which exhibit their protective properties through scavenging free radicals [25][26][27]. In addition to phenolics, plants may also contain antioxidant volatile oils, carotenoids, and vitamins [28].…”
Section: Phytochemical Screeningsupporting
confidence: 51%
“…This assumption in-line with others that majority of antioxidant compounds present in plants are secondary metabolitesphenolic compounds (tannins, flavonoids, and phenolic acids) which exhibit their protective properties through scavenging free radicals [25][26][27]. In addition to phenolics, plants may also contain antioxidant volatile oils, carotenoids, and vitamins [28].…”
Section: Phytochemical Screeningsupporting
confidence: 51%
“…The analogous results have also been reported in other bioactivities. Scurrula ferruginea stem extract gave a higher potency than leaf extract in antioxidant and antibacterial activity . Moreover, the highest total phenolic content and iron‐chelating ability among the three different plant parts extracts (leaf, stem, and flower) of S. ferruginea were also found to be in the stem.…”
Section: Resultsmentioning
confidence: 99%
“…In the stems, sugars were the main metabolites that might be because the stem is a vital organ for the plant in accumulating and storing of energy substances . However, the present obtained results indicated that S. ferruginea stems possessed a lower amount of flavonoids and phenolic compounds, which are contradicting with previous studies . It might be due to the different drying methods and extraction solvents employed herein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations